2018
DOI: 10.3390/hydrology5010016
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Condition and Management in Kano Region, Northwestern Nigeria

Abstract: This paper provides a broad overview of issues on groundwater condition and management in the Kano region of northwestern Nigeria. The aim is to recommend new management strategies that can ensure sustainable groundwater resource management in the region. To achieve the aim of the study, various studies on groundwater conducted in the region were reviewed and key issues were identified. The review revealed that groundwater availability varied between the Basement Complex and Chad Formation areas of the region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Therefore, these are the most important soils in the basin. The floodplains have extensive thick sealing clays which prohibit seepage (Tukur et al 2018).…”
Section: Soilsmentioning
confidence: 99%
“…Therefore, these are the most important soils in the basin. The floodplains have extensive thick sealing clays which prohibit seepage (Tukur et al 2018).…”
Section: Soilsmentioning
confidence: 99%
“…However, the direct recharge to groundwater is about 86 mm and 94 mm computed as mean direct recharge observed in the upstream of Wudil and between Wudil and Hadejia station, respectively. In another development, changes in climate and land use were particularly found to affect the surface water chemistry of the basin (Tukur et al 2018). Evidence is in the spatial differences in dominance of water quality classes with the doubtful water quality class being higher in Wudil and Hadejia ( Figure 5), where the latter was influenced by wastewater from municipalities of Kano and Wudil while the former was influenced by the effect of chemical fertilizers used in irrigation plots around Hadejia area.…”
Section: Discussionmentioning
confidence: 98%
“…The findings of Mustapha et al (2014) revealed that surface water freshness deteriorates more in the drier period than in the wetter period due to the effect of rainfall recharge and dilution capability. Based on the selected surface water quality parameters (pH, temperature, total suspended solids, NH4 þ -N, and NO3-N), Tukur et al (2018) investigated the spatial changes of surface and shallow groundwater quality along Hadejia River Basin. The results showed the order of concentration of surface water pollution class ranging from moderate .…”
Section: Surface Water Quality Statusmentioning
confidence: 99%
“…Tarauni has the same geology as Kano in general. According to Tukur et al (2018) the region extends over two major geological structures. The southern and western parts of the region are underlain by the Basement Complex rocks and the north-eastern part by the sedimentary Chad Formation.…”
Section: Location and Geology Of Study Areamentioning
confidence: 99%